Psychological stress during exercise: immunoendocrine and oxidative responses - Huang, Chun-Jung; Webb, Heather E; Evans, Ronald K; McCleod, Kelly A; Tangsilsat, Supatchara E; Kamimori, Gary H; Acevedo, Edmund O (Experimental biology and medicine (Maywood, N.J.), 2010)
The purpose of this study was to examine the changes in catecholamines (epinephrine [EPI] and norepinephrine [NE]), interleukin-2 (IL-2) and a biomarker of oxidative stress (8-isoprostane) in healthy individuals who were exposed to a dual challenge (physical and psychological stress). Furthermore, this study also examined the possible relationships between catecholamines (NE and EPI) and 8-isoprostane and between IL-2 and 8-isoprostane following a combined physical and psychological challenge. Seven healthy male subjects completed two experimental conditions. The exercise-alone condition (EAC) consisted of cycling at 60% VO(2max) for 37 min, while the dual-stress condition (DSC) included 20 min of a mental challenge while cycling. DSC showed greater EPI and 8-isoprostane levels (significant condition by time interaction). NE and IL-2 revealed significant change across time in both conditions. In addition, following dual stress, EPI area-under-the-curve (AUC) demonstrated a positive correlation with NE AUC and IL-2 AUC. NE AUC was positively correlated with IL-2 AUC and peak 8-isoprostane, and peak IL-2 was positively correlated with peak 8-isoprostane in response to a dual stress. The potential explanation for elevated oxidative stress during dual stress may be through the effects of the release of catecholamines and IL-2. These findings may further provide the potential explanation that dual stress alters physiological homeostasis in many occupations including firefighting, military operations and law enforcement. A greater understanding of these responses to stress can assist in finding strategies (e.g. exercise training) to overcome the inherent psychobiological challenges associated with physically and mentally demanding professions.